Penerapan Metode CPM dan PERT Pada Proyek Konstruksi Gereja Kemah Tabernake PIK 2 Jakarta Utara - Glisina Dwinoor Rembulan; Sun Yuhao (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2023)
PT. TCI is a company operating in the construction sector which handles the construction of several projects, one of which is the Tabernacle Church project. In carrying out the project work, several factors/problems arose, resulting in an extension of the project foundation construction stage and increasing the project period and costs. The use of the CPM and PERT methods for implementing the foundation construction of the GKT project using the planned and actual schedules has been able to optimize the work, namely 123 days using the planned schedule and 150 days using the actual schedule. These results have found the critical path, so that by applying the CPM and PERT methods in this project, an estimated schedule can be obtained to speed up the project. The cost difference using the CPM, PERT and CPM-PERT methods for the planned schedule is IDR 304,000,000 (Three Hundred and Four Million Rupiah) , Rp. 264,000,000 (Two Hundred and Sixty Four Million Rupiah) and Rp. 264,000,000 (Two Hundred and Sixty Four Million Rupiah). The difference in costs using the CPM, PERT, CPM-PERT method for the actual schedule is IDR 344,000,000 (Three Hundred Forty Four Million Rupiah), IDR 304,000,000 (Three Hundred Forty Four Million Rupiah) and IDR 304,000,000 (Three Hundred Forty Four Million Rupiah). These costs will be the contractor's profit.